The natural resource curse and fiscal decentralization - Perez-Sebastian, F; Raveh, O (University of Oxford, 2013)
Natural resource abundance is a blessing for some countries, but a curse for others. We show that differences across countries in the degree of fiscal decentralization can contribute to this divergent outcome. Using a large panel of countries, covering several decades and various fiscal decentralization and natural resource measures, we provide empirical support for the novel hypothesis. We also study a model that combines political and market mechanisms, under a unified framework, to illustrate how natural resource booms may create negative effects in fiscally decentralized nations.